Perioperative outcome in gynecological oncology surgeries: A single centre study - Lama, Jyoti Bhaju; Sharma, Umesh Kumar; Devkota, Mukti; Yadav, Birendra Kumar; Rai, Ujwal (Medical Journal of Eastern Nepal, 2025)
Background Gynaecological cancers constitute a major cancer burden globally. So the service demand in gynaecology oncology is increasing day by day. The gynecological cancers where surgical intervention may be needed are cervical, uterine or endometrial, ovarian, vulvar, and vaginal cancers and the procedures may range from staging, debulking surgeries involving multiple visceral organs resections, total/radical hysterectomy, lymphadenectomy, vulvectomy and vaginectomy. Due to the complexity of these surgeries and patient-related factors, complications are common. This study evaluates intraoperative and postoperative complications in gynecological cancer surgeries at Purbanchal Cancer Hospital, Birtamode. Methods This prospective study was conducted in the Department of Gynecology Oncology at Purbanchal Cancer Hospital from July 2023 to January 2025. A total of 70 patients diagnosed with or suspected of having gynecological cancer were included. Data were collected from the hospital electronic medical records regarding patients profile, surgery type, operative time, intraoperative events, blood loss, complications, and hospital stay. The primary outcomes were intraoperative and postoperative morbidity, measured through the Clavien-Dindo classification of surgical complications. The secondary outcome were patient profile, average hospital stay and blood loss. Results Among the 70 surgeries performed, the most common were staging laparotomies (34), debulking surgeries (17), and radical hysterectomies (11). The average patient age was 51-60 years, with 88% being parous and 60% menopausal. The mean operative time was 270 minutes, with majority (38.5%) of patients experiencing blood loss between 200-300 ml. Clavin Dindo scoring for surgical complications stratification was done and 68% of the patients had CD score 1 followed by CD 2 which constituted 32%. Intraoperative complications included bowel injury (7.1%), bladder injury (5.5%), and vessel injury (1.3%). Postoperative complications included urinary tract infections (5.5%), paralytic ileus (2.6%), chest infections (4.2%), chyluria (1.3%) and secondary haemorrhage (1.3%). The average hospital stay was 8 days. Conclusion Gynecological oncology surgeries are complex, with notable intraoperative and postoperative complications. Multidisciplinary care, prehabilitation, and proper postoperative management are essential in reducing morbidity and improving outcomes. The surgical complication rates in this study are consistent with similar large studies.